Integrating Socio-Ecological Criteria into Early-Stage Product Development - Arnardóttir, Eygló Anna; Oguz, Selin (My University, 2026)
Integrating socio-ecological criteria into early-stage product development remains challenging due to limited data availability and uncertainty. This thesis aims to address this issue at GKN Aerospace by developing a prioritised list of socio-ecological criteria and an accompanying integration framework for practical application in the early stages of product development. The purpose is to support trade-off scenarios and embed socio-ecological aspects into the design process. Through a semi-systematic literature review, an initial list of 263 criteria was collected and funnelled down to 41 through aggregation and guided filtering with sustainability experts. In parallel, interviews were conducted with practitioners at GKN Aerospace to identify gaps and integration opportunities in the company’s current product development processes. An additional literature review identified criteria prioritisation methods, from which expert opinion and the DEMATEL method were adapted to evaluate criteria importance and interdependencies. Through the prioritisation and mapping of company processes, 16 primary and 25 case-by-case criteria were proposed for integration into product requirements and concept selection matrices. The framework and criteria were validated through interviews with practitioners and life-cycle-focused academic research. The validation confirmed the importance of prioritising criteria that impact the use phase, to which over 90% of the product-related emissions can currently be attributed. In addition, there is an opportunity to ensure more robust compliance with sustainability-related regulations by embedding them into product requirements. Further research should focus on developing measurable metrics and assessment methods for each criterion to support their practical implementation in the design process
Keywords: Sustainable Product Development; Socio-Ecological Criteria; Early-Stage Product Development; Aerospace Industry; Concept Selection; Product Requirements